2020
DOI: 10.1016/j.icarus.2020.113779
|View full text |Cite
|
Sign up to set email alerts
|

Venus: A phase equilibria approach to model surface alteration as a function of rock composition, oxygen- and sulfur fugacities

Abstract: Venus: A phase equilibria approach to model surface alteration as a function of rock composition, oxygen-and sulfur fugacities. Icarus, 346, article no. 113779.For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 94 publications
(202 reference statements)
2
19
1
Order By: Relevance
“…The formation of these phases is further suggested by the oxygen fugacity models by Semprich et al. (2020) and suggested in other studies, but not observed on our samples (Berger et al., 2019; Fegley et al., 1992; Gilmore et al., 2017; Yu, 2007; 2018; Zolotov, 2015, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The formation of these phases is further suggested by the oxygen fugacity models by Semprich et al. (2020) and suggested in other studies, but not observed on our samples (Berger et al., 2019; Fegley et al., 1992; Gilmore et al., 2017; Yu, 2007; 2018; Zolotov, 2015, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Pyrite (FeS 2 ), for example, was demonstrated to be unstable in the current Venus climate regime by , yet was and is considered as part of a possible climate model (Hashimoto & Abe, 2005;Klose et al, 1992;Wood, 1997). It is currently suggested that pyrite may be causing the radar anomaly that was first revealed in Venera radar data, and later observed in Magellan SAR data (Port et al, 2020;Schaefer & Fegley, 2004;Semprich et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected from theory that materials with high dielectric constants will enhance their radar reflectivity and lower their radar emissivity (Campbell, 1994; Pettengill et al., 1992). Proposed minerals include: (1) pyrite produced through sulfidation and/or oxidation of iron (Berger et al., 2019; Klose et al., 1992; Kohler, 2016; Pettengill et al., 1988; Port et al., 2016; Sempich et al., 2020; Wood & Brett, 1997), (2) coatings formed by condensation onto the rock as “metallic frosts” like lead and bismuth sulfides (Brackett et al., 1995; Kohler et al., 2015; Pettengill et al., 1996; Port et al., 2020; Schaefer & Fegley, 2004), and (3) ferroelectrics (e.g., perovskite or chlorapatite) that become highly conductive at certain temperatures (Arvidson et al., 1994; Shepard et al., 1994; Treiman et al., 2016). These reactions are a function of rock composition, atmospheric composition, temperature, and degree of weathering or surface age.…”
Section: Introductionmentioning
confidence: 99%
“…These radar “anomalies” are ascribed to the presence of minerals with a high dielectric constant, as it is expected from theory that materials with high dielectric constants will enhance their radar reflectivity and lower their radar emissivity (Campbell, 1994; Pettengill et al., 1992). Several studies indicate that high dielectric minerals can be produced through chemical weathering reactions between the rocks and the near‐surface atmosphere (e.g., Klose et al., 1992; Schaefer & Fegley, 2004; Semprich et al., 2020; Treiman et al., 2016 and references therein); if so, the reduction in radar emissivity can be associated with the formation of high dielectric minerals over time and thus can serve as a chronometer.…”
Section: Magellan Emissivity As a Chronometermentioning
confidence: 99%